Listen to me Marlon [videorecording (DVD)] - Riley, Stevan; Brando, Marlon (Showtime, 2018)
With exclusive access to personal archive, this is the definitive Marlon Brando cinema documentary. Charting his exceptional career as an actor and extraordinary life away from the stage and screen; the film will fully explore the complexities of the man by telling the story uniquely from Marlon's perspective. There are no interviewers, no talking heads, just Marlon guiding us in this creative odyssey into the mind and motivation of an enigma.